Sustainable Competitive Advantage: Transforming Green Practices Into Batik SME Performance - Srikalimah Srikalimah; Ahmad Idris; Taufik Akbar; Nuril Aulia Munawaroh; Miftahul Munir (Owner : Riset dan Jurnal Akuntansi, 2025)
This study analyzes how green entrepreneurship (GE) and sustainable business management (GBM) affect the performance of natural-dye batik SMEs., with sustainable competitive advantage (SCA) serving as a mediating factor. The research population consists of 48 natural-dye batik MSMEs in Kediri registered with relevant institutions. A saturated sampling technique was applied, making the entire population the research sample. The research utilized Structural Equation Modeling-Partial Least Squares (SEM-PLS) to quantitatively investigate both direct effects and mediated relationships among variables. The findings indicate that GE and GBM have no significant direct effect on BP or SCA. Conversely, SCA has a significant positive effect on BP and fully mediates the influence of GE on BP as well as GBM on BP. The study underlines that improvements in business performance through green entrepreneurship and green business management are achieved only if such practices are first shaped into sustainable competitive advantage. These results provide empirical support for the Natural Resource-Based View (NRBV), highlighting that environmental strategies yield sustainable performance only when coupled with inimitable organizational capabilities and provides practical implications for batik MSMEs to focus on product differentiation, innovation, and eco-branding.